Legal Certainty of Suspension of Detention with Guarantee under Article 110 of the Indonesian Criminal Procedure Code - Rakhmat Makhmudin; Alip Rahman; Siska Karina (Inovasi Pratama Internasional. Ltd, 2027)
The enactment of Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code (KUHAP) introduces significant reforms to criminal procedural law, including the regulation of suspension of detention with guarantee under Article 110. Although the provision seeks to strengthen procedural safeguards and the protection of suspects' rights, questions remain regarding its ability to ensure legal certainty in practical implementation. This study aims to analyze the normative regulation of suspension of detention with guarantee under Article 110 and evaluate whether the provision provides adequate legal certainty within Indonesia's criminal justice system. This research employs normative legal research using statutory, conceptual, and comparative approaches. Primary legal materials consist of Law Number 20 of 2025 and related legislation, while secondary legal materials include recent scholarly publications on criminal procedure, detention, due process of law, legal certainty, and human rights. The collected legal materials were analyzed qualitatively through descriptive, interpretative, and evaluative legal analysis. The findings reveal that Article 110 establishes a more comprehensive legal framework than the previous Criminal Procedure Code by reaffirming the authority to grant suspension of detention, recognizing monetary and personal guarantees, and strengthening procedural safeguards. However, the provision has not yet achieved complete legal certainty because it lacks objective statutory criteria governing the approval of applications, proportional guarantee standards, and measurable parameters for the exercise of official discretion. Consequently, inconsistent interpretation and unequal application remain potential challenges in practice. The novelty of this study lies in its normative evaluation of Article 110 from the perspective of legal certainty following the enactment of the new Criminal Procedure Code. The study recommends the adoption of implementing regulations or judicial guidelines establishing objective procedural standards to ensure consistent application while strengthening due process of law and the protection of suspects' rights